O ordenamento jurídico de reformas no ensino médio no Brasil: pretexto, contexto e texto - Ferro, Karla Érika Ferreira (2024)
This study deals with an analysis of the legal/normative framework that guided, from the year 1930 onwards, the reforms promoted in the stage of basic education today called Secondary Education, contextualizing these changes in educational legislation with the historical moment and class interests that guide these changes. Understanding these aspects is crucial to elucidate what type of training is historically aimed at the working class and thus strengthen resistance to these educational policies that focus on the reproduction of capital to the detriment of an emancipatory education. This study's general objective is to carry out a critical analysis of the normative regulations that guided secondary education reforms from 1930 onwards, contextualizing the class interests involved. As specific objectives, we list: a) Carry out an exhibition of the first approaches between work, education and law; b) identify the main legal- normative documents of each period of secondary education reform (years 1930-61; 1964-85; 1990 to the present; c) analyze the historical and economic context of each period; d) point out the link between legal regulations and the type of training offered to the working class, with an emphasis on the educational dualism2 present in class societies, such as Brazil. For an investigation with the intended breadth, it is necessary to consider the social being in its entirety and historicity. Thus, bearing in mind that the movement of being in its processuality is what must determine the movement of the researcher, the Marxian ontomethod will be applied to the research, which will be from a historical-dialectic materialist perspective, of the documentary and bibliographic type. The main documents analyzed are laws, ordinances and decrees, such as decree-Law no 4,244/42; Law no 5692/71; Law No. 9394/96 and Law No. 13,415/17, among others. In addition to the documents, this research is based on the work of authors such as: Marx (2009, 2021); Lukács (1967, 2018); Mészáros (2009,2011), Tonet (2012, 2013); Saviani (2004, 2019); Kuenzer (2009, 2013); Santos (2017); Maia Filho (2004); Machado (1989).